PROTOCOL: Interventions to improve outdoor mobility among adults with disability. Issue 4 (6th October 2022) - Ringsten, Martin; Iwarsson, Susanne; Lexell, Eva Månsson
Abstract: This is the protocol for a Campbell systematic review. The objectives are as follows: to assess the efficacy of interventions aiming to improve outdoor mobility for people with disability and to explore if the efficacy varies between different populations and different intervention components.